Development of a Multi-Motor Power System for Vehicles Converted to Electric - Zapata Sebastian, Correa; Crismatt Carlos, Vergara; Mesa Edgar, Rico (International Journal of Engineering and Technology, 2018)
The GACIPE research group has been developing a project focused on the conversion of an internal combustion car to an electric one, implementing a mechanical and electronic development with the objective of implementing new technologies in the automotive sector by designing drivers to control the speed of multiple 2.2 kw DC motors with a new trigger procedure of the power devices. This project is a small contribution to reducing the effects of climate change. Â Â